PENERAPAN MODEL KOOPERATIF TGT (TEAM GAMES TOURNAMENT) UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATERI BANGUN RUANG DI KELAS V SDN 55/I SRIDADI - Niki Azura; Muhammad Sofwan; Akhmad Faisal Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstrak This research is a Classroom Action Research (CAR) that aims to improve the learning activity of fifth grade students of SDN 55/I Sridadi through the Team Games Tournament (TGT) learning model. Data collection methods used observation, interviews, and documentation, analyzed quantitatively and qualitatively. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results showed that the implementation of the TGT model has increased student activity. In cycle I, meeting 1, student activity was 52.13% (low category), increasing in meeting 2 to 59.37% (low category) with an increase of 7.24%. In cycle II, meeting 1 reached 63.15% (sufficient category) with an increase of 3.78% from the previous meeting, and in meeting 2 it increased to 78.28% (high category) with an increase of 15.13%. The implementation of the TGT model makes students more active, brave, and independent in exploring knowledge through observation, asking teachers and friends, discussing, and presenting in front of the class. The conclusion of this study is that the TGT model is effective in increasing the activeness of fifth grade students in spatial geometry material, as evidenced by the increase in the percentage of activeness at each meeting in both cycles.